Effect of ascorbate on the activity of hypoxia-inducible factor in cancer cells. - Knowles, H; Raval, R; Harris, A; Ratcliffe, P (2003)
Hypoxia-inducible factor (HIF) plays an important role in determining patterns of gene expression in cancer. HIF is down-regulated in oxygenated cells by a series of Fe (II) and 2-oxoglutarate dependent dioxygenases that hydroxylate specific residues in the regulatory HIF-alpha subunits. Because these enzymes require ascorbate for activity in vitro we analyzed the effects of ascorbate on HIF in human cancer cell lines. Ascorbate at physiological concentrations (25 micro M) strikingly suppressed HIF-1alpha protein levels and HIF transcriptional targets, particularly when the system was oncogenically activated in normoxic cells. Similar results were obtained with iron supplementation. These results indicate that both ascorbate and iron availability have major effects on HIF, and imply that the system is commonly regulated by limiting hydroxylase activity under normoxic tissue culture conditions.